Molecular characterization and clinical presentation of HKαα and anti‐HKαα alleles in southern Chinese subjects. (10th October 2012) - Shang, X; Li, Q; Cai, R; Huang, J; Wei, X; Xu, X
<x xml:space="preserve">Abstract</x> The HKαα allele is a rearrangement occurring in the α‐globin gene cluster containing both the ‐α3.7 and αααanti4.2 unequal crossover junctions. The anti‐HKαα allele is the reciprocal product containing both the ‐α4.2 and αααanti3.7 unequal crossover junctions, which had been predicted but had not been detected previously. The phenotypic feature and population frequency of these two unusual alleles were not described. We report the identification of nine individuals carrying the HKαα allele and two individuals carrying the anti‐HKαα allele in southern China and describe their phenotype and haplotype data. The molecular structures of HKαα allele and anti‐HKαα allele were confirmed by two‐round nested polymerase chain reaction assay. The mechanism of origin of both alleles is related to probably simultaneous double crossover. Heterozygotes of HKαα or anti‐HKαα allele show a normal hematological phenotype. Finally, we report the carrier rates of these both alleles in the Guangxi Zhuang Autonomous Region of southern China, namely, ∼0.07% for the HKαα allele and ∼0.02% for the anti‐HKαα allele.